PENGELOLAAN DANA DESA DALAM PEMBANGUNAN DI DESA PASLATEN KECAMATAN LANGOWAN BARAT KABUPATEN MINAHASA - WALANGITAN, MARSELA; LENGKONG, FLORENCE; KOLONDAM, HELLY (Sam Ratulangi University, 2019)
In realizing the objectives of the development program in each institution it takes a managerialpattern in the management of development and other governmental programs to be perceived and enjoyedby the community. The use of village funds is prioritized in village development. One of the most importantthings needed is the wisdom of the village head to direct and guide the community to jointly implement thedevelopment program. The purpose of this research is to know how the Management Of Village Funds InDevelopment In Paslaten Village Langowan West District Minahasa Regency. The research methods usedin this study are qualitative methods. The informant in the research is a person who can provide informationabout the situation and background conditions of research. The focus of research is seen from the indicatoraccording to George Terry, which is planning, organizing, mobilization and controlling. Data collectiontechniques through observation, interviews, and documentation. The results showed that the ManagementOf Village Funds In Development In Paslaten Village Langowan West District Minahasa Regency in themanagement of village funds is not done transparently or openly to every community even a lot of issuesCommunity that the management of village funds in the use of village funds is not suitable for it.Keywords : Management, Village Funds, Development.